ANALISIS KONSENTRASI BELAJAR SISWA KELAS 4 PADA MATA PELAJARAN BAHASA INDONESIA DI SDN SEMANAN 09 PAGI JAKARTA BARAT - Sabillal Irfan Mulyana Putra; Enawar; Sunaryo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Learning concentration is a crucial aspect that determines students’ success in mastering lessons, particularly in Bahasa Indonesia which requires integrated skills of listening, reading, writing, and speaking. However, not all students are able to maintain consistent focus during classroom activities. This study aims to analyze the forms of learning concentration among fourth-grade students at SDN Semanan 09 Pagi, West Jakarta, and to identify the factors that influence it. A descriptive qualitative approach with a case study method was employed, using observation, interviews, and documentation with the classroom teacher and five students with diverse characteristics. The research instruments covered several concentration indicators, including visual focus, attention, verbal responses, answering ability, willingness to express opinions, and psychomotor responses. The findings reveal variations in students’ concentration levels. Some students demonstrated strong focus through active participation in discussions, asking questions, and showing discipline in taking notes and submitting assignments. In contrast, others were easily distracted, lacked confidence in expressing opinions, and tended to be active only when directed by the teacher. Both internal factors, such as motivation and interest, and external factors, including teaching strategies, learning media, and classroom conditions, were found to influence concentration quality. These findings highlight the importance of teacher creativity in designing interactive learning strategies to encourage students to stay focused, express their thoughts, and become more independent learners.